Hubungan Pengetahuan dan Keterpaparan Informasi dengan Tindakan Pencegahan Keputihan Pada Remaja Putri di SMK Wahyu 1 Makassar - Chitra Dewi; Marisna Eka Yulianita; Annisa Khaerani (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2022)
Indonesia is a tropical country that allows 75% of the female population to experience vaginal discharge. The purpose of this study was to determine the relationship between knowledge and information exposure with the prevention of vaginal discharge in adolescent girls. This type of research was a quantitative using an analytical survey with a cross sectional approach. The population is 111 people with a sample of 86 students using stratified random sampling technique. This research was carried out at SMK Wahyu 1 Makassar on November 11-11 December 2019. The results showed that respondents who had good knowledge of vaginal discharge prevention were 47 (54,7%) respondents. Good information’s exposure about the prevention of vaginal discharge were 50 (58,1%). respondents who took steps to prevent vaginal discharge were 45 (52,3%). Chi square statistical test results obtained ρ value =0.000 (ρ<α). There is a relationship between knowledge and prevention of vaginal discharge and there is a relationship between information exposure and prevention of vaginal discharge in adolescent girls. The conclusion of this study is that most of the students have sufficient knowledge and good information’s exposure about the prevention of vaginal discharge, and have a good vaginal discharge prevention effort.